Analisis Keterkaitan Gaya Belajar Visual Auditori Kinesteteik pada Pembelajaran SBdP Kelas IV SDN Buara 02 - Uswatun Khasanah; Moh Toharudin; Laelia Nurpratiwiningsih (Journal on Education, 2024)
Teachers often do not apply learning strategies that suit students' learning styles. This is very important, especially in learning Arts, Culture and Crafts (SBdP). This research aims to analyze the relationship between learning styles in SBdP class IV SDN Buara 02. This research focuses on the role of teachers in SBdP learning, student obstacles and teacher solutions so that learning runs well. Researchers used qualitative methods with a case study approach. Data collection techniques include observation, interviews and documentation. The results of this research are that teachers play a very active role in learning activities with students and teachers also pay attention to the learning styles of students and implement the three visual auditory kinesthetic learning styles in one learning time. The teacher's role is very important in SBdP learning. The teacher is not only the main source so that learning runs smoothly, but also acts as a facilitator who meets all the needs of students during learning activities.